The Association between Serum Irisin Concentration and Ischemic Stroke: From Aetiology to Clinic: Serum Irisin and Ischemic Stroke - ÇALIK, Mustafa; Sengul , Yildizhan; Gürkan , Zahide Mail; Hintoğlu , Deniz; Mısırlıoğlu, Naile Fevziye; Uzun, Hafize (Journal of Medical Biochemistry, 2022)
Aim: To investigate the relationship between irisin levels in serum and classification of subtype of acute ischemic stroke, National Institutes of Health Stroke Scale (NIHSS) and Modified Rankin Score (mRS) at the time of discharge from the hospital in Turkish patients who had their first acute ischemic stroke (AIS). Methods: Our study was initiated by recruiting 180 patients who applied to our emergency department with the diagnosis of AIS from May 2021 to November 2021. This study was designed as a prospective cross-sectional study. Results: A significant relationship was found between serum irisin levels and ischemic stroke aetiological factors (TAOST) (p=0.017). Increased serum irisin levels were detected in patients without neurological deficits with localization value than those with it (p
Keywords: Acute ischemic stroke, irisin, National Institutes of Health Stroke Scale, aetiology